Diminished Value Discrimination in Obsessive-Compulsive Disorder: A Prospect Theory Model of Decision-Making Under Risk - George, Sophie A.; Sheynin, Jony; Gonzalez, Richard; Liberzon, Israel; Abelson, James L. (Frontiers in Psychiatry, 2019)
Introduction: It has been hypothesized that people diagnosed with anxiety and obsessive-compulsive disorder (OCD) exhibit behavioral aberrations when faced with the potential for negative outcomes, but the specific cognitive aspects of decision-making that may be altered have not been systematically studied in clinical populations. Here, we studied decision-making in a clinical cohort using a task that allows for examination of the subjective perceptions of values and probabilities associated with different choice outcomes. Methods: Patients diagnosed with OCD (n=10), generalized anxiety disorder (n=15), social anxiety disorder (n=14), and healthy controls (n=20) were given a decision-making task and choices were modeled using a cumulative prospect theory framework. Results: We found OCD patients to have lower value discrimination than controls, as well as less optimal performance on the task, an effect that was mostly driven by trials with only positive outcomes. Discussion: Our results shed light on the cognitive processes that drive altered decision-making under risk in OCD. Specifically, they demonstrate that OCD patients have diminished sensitivity to positive outcomes, which might be associated with risk aversion and altered reward processing. These findings also extend prior reports, suggesting that altered cognitive processing during decision-making is linked to altered perception of value, but not probability, in these patients.